Cystic Extramedullary Ependymoma - Graça, J.; Gültaşli, N.; D’Haene, N.; Brotchi, J.; Salmon, I.; Balériaux, D. (American Journal of Neuroradiology, 2006)
SUMMARY:Intradural extramedullary location of ependymoma is rare. To the best of our knowledge, only 9 cases have been described in the literature. We report a case of a histologically confirmed ependymoma (WHO grade II) presented in the MR imaging as a cystic, nonenhancing thoracic intradural extramedullary lesion compressing the spinal cord. The cystic appearance mimicking an arachnoid cyst at diagnosis and the leptomeningeal dissemination developed later were peculiarities that have never been previously described in relation to these rare tumors.